Correction of Vaginal Prolapse in a Pregnant EWE: A Case Report - Y. A., Wahab; S.O., Olayinka; O.K., Olofintuyi; L.O., Raji; K.A., Tijani (International Journal of Environment, Agriculture and Biotechnology, 2019)
This case report describes a successful correction of vaginalprolapse in a pregnant ewe in her last trimester. The prolapse was noticed some days following abrupt change in feed. On physical examination, the sheep was depressed and recumbent with intermittent straining. Epidural anaesthesia was achieved via administration of lidocaine into the first intercoccygeal space. The swollen and edematous prolapse was cleaned and decontaminated using mild potassium permanganate, after which the prolapse was repositioned and purse string suture was applied on the vulva for retention purpose. The animal was placed on antibiotics for 5 consecutive days to prevent secondary bacterial infection and the suture material was removed on the 8th day with no signs of recurrence. The sheep delivered precisely a week after the suture was removed with no complications. In conclusion, this report has shown detail of a successful correction of vaginal prolapse in a pregnant ewe.